2017
DOI: 10.1111/bph.13714
|View full text |Cite
|
Sign up to set email alerts
|

Rapid antidepressant effect of ketamine correlates with astroglial plasticity in the hippocampus

Abstract: BACKGROUND AND PURPOSEAstroglia contribute to the pathophysiology of major depression and antidepressant drugs act by modulating synaptic plasticity; therefore, the present study investigated whether the fast antidepressant action of ketamine is reflected in a rapid alteration of the astrocytes' morphology in a genetic animal model of depression. EXPERIMENTAL APPROACHS-Ketamine (15 mg·kg À1 ) or saline was administered as a single injection to Flinders Line (FSL/ FRL) rats. Twenty-four hours after the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 62 publications
0
39
0
1
Order By: Relevance
“…The present findings were in line with those of a clinical study in which increased hippocampal volumes were observed in patients who achieved remission following an infusion of ketamine, yet the study reported that the increased volumes were localized to the left side 18 . Animal studies also found that a single ketamine injection could induce increased volumes of the hippocampal CA1 and GCL regions twenty-four hours after the treatment in FSL rats 16 , and reverse the reduction of the number of granule cells in FSL-treated rats 30 . These findings support that rapid hippocampal structural plasticity induced by ketamine may be a potential mechanism underlying its fast antidepressant action.…”
Section: Discussionmentioning
confidence: 92%
“…The present findings were in line with those of a clinical study in which increased hippocampal volumes were observed in patients who achieved remission following an infusion of ketamine, yet the study reported that the increased volumes were localized to the left side 18 . Animal studies also found that a single ketamine injection could induce increased volumes of the hippocampal CA1 and GCL regions twenty-four hours after the treatment in FSL rats 16 , and reverse the reduction of the number of granule cells in FSL-treated rats 30 . These findings support that rapid hippocampal structural plasticity induced by ketamine may be a potential mechanism underlying its fast antidepressant action.…”
Section: Discussionmentioning
confidence: 92%
“…Stereological analysis has shown that the volume of glial fibrillary acidic protein positive astrocytes is significantly lower in the hippocampus of Flinders Sensitive Line rats, which spontaneously develop a depression‐like phenotype (Ardalan et al . ). In this study, labeling in glutamate‐C4 (−27%) and glutamine‐C4 (−25%) from [2‐ 13 C]acetate in PFC of SD mice was reduced as compared with controls.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, we observed a positive correlation between changes in the astrocyte morphology including the lower number of astrocyte branches and hippocampal volume loss 4 days following SAH. It has been suggested that conditions which involve glial remodeling are associated with changes in the hippocampus volume ( Czeh and Lucassen, 2007 ), and a recent publication of our group indicated that changes in the volume of the hippocampus are correlated with the morphological alteration of astrocytes ( Ardalan et al, 2017 ). Therefore, we proposed that the observed hippocampal shrinkage in the SAH animals might reflect microstructural changes including astrocytes.…”
Section: Discussionmentioning
confidence: 99%